Evaluación de 3 niveles de láminas de riego por goteo en el cultivo de espárrago (Asparagus officinalis L.) UC 115 y su efecto en la producción y calidad, en el fundo Agualima SAC – irrigación Chavimochic - Cabanillas Valera, Abrahán Rafael (2019)
The present research work was carried out in the "Agualima" farm owned by Agualima S.A.C, located in Panamericana Norte km 514, Virú District, Virú Province, Libertad Department. Geographically the fundo is located at -8.44885823 south latitude and -78.727039 west longitude of the Greenwich meridian. The experiment was carried out in fields of asparagus (Asparagus Officinalis L.) already established, under the drip irrigation system. The cultivar used was UC 115 F1; with an age 2.5 years (4th season), the density used was 25000 plants / Ha with distance between rows 2.4 m and between plants of 0.40 m in double row. The soils presented a sandy texture, with neutral reaction, very low content of organic matter, high content of phosphorus, low potassium content and low electrical conductivity. The temperatures during the experiment fluctuated between 18 ° C and 19 ° C. The average temperature was 18.5 ° C, the relative humidity averaged 82. The treatments have been to evaluate three irrigation sheets: TREATMENT A (control irrigation): E0 tank (Accumulated) and the control frequency and Kc predetermined; TREATMENT B (Daily watering): the tank evaporation (E0) daily and the daily frec and Kc predetermined are taken into account; TREATMENT C (inter-day irrigation): tank evaporation (E0) (Accumulated) and interdiária frec and predetermined Kc, with three repetitions are taken into account. The variables were evaluated according to the experimental design of blocks completely randomized with three treatments and three repetitions. It was concluded that the yields of shoots obtained from the tank irrigation sheets and the determined kc did not significantly influence the weight and quality parameters of the asparagus.